HIV/AIDS messaging in Germany and Nigeria: A corpus linguistics study - Antia, Bassey E.; Razum, Oliver (Stellenbosch Papers in Linguistics Plus, 2013)
Modelling success in HIV messaging is notoriously difficult in part because of the diversity of disciplines interested in the subject (e.g. public health, psychology, communication, education, sociology, linguistics) and the claims made in each, often on the basis of different coming-to-know processes. For instance, although relevant research in public health and communication emphasizes audience responses but sometimes slights detailed analyses of texts, work in applied linguistics tends to engage with texts without, however, framing its claims in the context of theories of behaviour. This study makes a case for attention to both text and behaviour by showing how a corpus linguistics study of texts of HIV messaging can be accommodated within a behavioural framework. A corpus of HIV messages from Germany and Nigeria, analyzed from the standpoint of predictions of a behavioural theory, suggests that only two German messages and one Nigerian message (out of the eleven messages in each national corpus) had the mix of features (high threat, high efficacy) predicted by the model to elicit message acceptance. In view of the implication that the observed nexus between messaging and society does not necessarily translate into better acceptance prospects as defined within the particular behavioural theory, this study may be seen as problematising certain claims in applied linguistics research on HIV, especially recommendations dealing with the need for messaging to reflect local (knowledge) perspectives.